Anticataract Effect of the Aqueous Extract of the Flowers of Aspilia africana in Murine Model of Diabetic and Age-Related Cataracts - Adwoa Frema Amanfo; Samuel Kyei; Yaw Duah Boakye; Clement Osei Akoto; Justice Kwaku Addo; Kofi Oduro Yeboah; Newman Osafo (Hindawi Limited, 2023)
Background. The use of Aspilia africana in traditional medicine for the management of ocular diseases has been reported in India and some indigenous communities of Africa. The aim of this study was to investigate the aqueous extract of the flowers of A. africana (AAE) as an anticataract remedy using murine models of diabetic and senile cataracts. Methods. Preliminary phytochemical screening of the extract, in vitro antioxidant assays, and in vitro aldose reductase inhibitory activity were performed. For anticataract investigations of the extracts, diabetic cataract was induced by galactose administration in 3-week-old Sprague Dawley rats. The evaluation of experimentally induced age-related cataract was performed by administering sodium selenite to 10-day-old rat pups. Results. The phytochemical analysis revealed the presence of alkaloids, tannins, flavonoids, glycosides, and saponins. In vitro aldose reductase inhibitory property of the extract on rat lenses revealed that the AAE inhibited the enzyme activity with IC50 of 12.12 µg/ml. For the anticataract investigations, 30, 100, and 300 mg·kg−1AAE-treated rats recorded significantly low (p≤0.0001) cataract scores compared to the negative control rats, indicating a delay in cataractogenesis from the second week of treatment in the galactose-induced cataractogenesis. Similarly, the treatment with AAE caused a significant reduction (p≤0.0001) in cataract scores compared to the negative control rats in the selenite-induced cataractogenesis. Markers of lens transparency, such as aquaporin 0, alpha-A crystallin, and total lens proteins and lens glutathione levels, were significantly preserved (p≤0.05-0.0001) in each cataract model after AAE treatment. Conclusion. The study established the anticataract potential of the aqueous extract of flowers of A. africana in murine models, hence giving scientific credence to its folkloric use in the management of cataract.